Extracellular localization of napin in the embryogenic tissues of Brassica napus spp. oleifera - Namasivayam, Parameswari; Skepper, Jeremy Neil; Hanke, David E. (Springer, 2008)
Napin, a storage protein, has been reported to be transcribed abundantly during the pre-embryogenic stage and associated with the induction of Brassica napus secondary embryogenesis. In this study, we studied the distribution pattern of napin in the winter oilseed rape embryogenic tissue in comparison to that of the non-embryogenic tissue using the indirect immunofluorescence localisation coupled with the ultrastructural immunogold labelling techniques. Immunolocalisation studies revealed that the extracellular matrix layer outside the outer epidermal cell wall of B. napus embryogenic tissues contained napin. This is the first study to report the extracellular localisation of napin. In addition, we have also further characterised the expression pattern of Eg1 that encodes for napin in the B. napus embryogenic tissue.